(NrAZRU[ENIE DREWESINY SOSNY W PO^WE (B:s (Nw USLOWIQH sREDNEJ sIBIRI (B/s - (NpETRENKO(B, (NiNGA aLEKSANDROWNAs; (NsINADSKIJ(B, (N`(B.(Nws; (NaKADEMIQ NAUK sssr(B.s (NsIBIRSKOE OTDELENIE(B. (NiNSTITUT LESA I DREWESINY IM(B. (Nw(B.(Nn(B. (NsUKA^EWAs ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1973)
(NzAKL(B.: (NS(B. 170-173s
(NlIT(B.: (NS(B. 174-190s
Keywords: (NmIKROBIOLOGIQ PO^Ws